The Relationship Between Anxiety Levels and Adaptive Abilities of New Students at Islamic Boarding Schools - Arrohman Mahfudz; Nopi Nur Khasanah; Kurnia Wijayanti (International Journal Of Health Science, 2026)
The adaptation process within the Islamic boarding school (pondok pesantren) environment often poses a significant challenge for new students. Factors such as separation from family, academic demands, and strict rules can trigger anxiety. This anxiety potentially hinders the student's ability to adjust and may lead to psychosocial problems. This study aims to analyze and prove the relationship between the level of anxiety and the adaptation ability of new students at Pondok Pesantren Kun Assalam, Semarang. To analyze the relationship between anxiety levels and the adaptability of new students (santri) at Kun Assalam Islamic Boarding School, Semarang. This research employed a correlational design with a cross-sectional approach. The entire population and sample consisted of 80 new students at Pondok Pesantren Kun Assalam, utilizing a total sampling technique. The instruments used were the Zung Self-Rating Anxiety Scale (SAS/ZRAS) questionnaire to measure anxiety and an adaptation ability questionnaire. Data analysis was performed using the Spearman's rho correlation test. The majority of respondents were in the 7–12 years age group (75%). Univariate results showed that most students were categorized as not anxious (86.4%), yet 70% of them exhibited poor adaptation ability. The correlation test found a significant negative correlation between the anxiety level and adaptation ability (p-value = 0.000; $α$ < 0.05). The strength of the relationship was moderate (r = -0.506). These findings indicate that the higher the level of anxiety experienced by the students, the lower their adaptation ability.